1993
DOI: 10.1080/10825541.1993.11670018
|View full text |Cite
|
Sign up to set email alerts
|

Gaining and Losing Voice: A Longitudinal Study of Students' Continuing Impulse to Learn Across Elementary and Middle Level Contexts

Abstract: This research traces students' perceptions of their experiences as they moved from a whole language elementary classroom, in which they actively participated as knowers, into subsequent experiences in a departmentalized junior high school. The study was framed by a constructivist definition of intrinsic motivation: the continuing impulse to learn. Students' motivation to learn in their elementary classroom was connected to their own empowerment through three interactive elements: (a) a condition ofhonored voic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
9

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 23 publications
0
31
0
9
Order By: Relevance
“…On the other hand, Oldfather and McLaughlin (1993) held peer influence, Among other factors, as a predictor of academic achievement. One explanation for the divergent findings could be the perception of teacher's education, especially, in Nigeria.…”
Section: Summary and Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Oldfather and McLaughlin (1993) held peer influence, Among other factors, as a predictor of academic achievement. One explanation for the divergent findings could be the perception of teacher's education, especially, in Nigeria.…”
Section: Summary and Discussion Of Findingsmentioning
confidence: 99%
“…Oldfather and McLaughlin (1993) in their study found that students are motivated to learn in classrooms where teachers impress the students that they can make it, where teachers praise and encourage students for efforts made and where teachers encourage students not only to compete with others but also to compete with themselves. They confirmed that when students are taught in this manner, they are always motivated to learn to fulfil their teachers' prophecy that they can make it.…”
Section: Students' Interestmentioning
confidence: 99%
“…The research is less clear, however, on the shifts that occur in students' motivation to read over time. Although decreases in intrinsic reading motivation have been noted as children move from the elementary grades to middle school, explanations vary as to the cause, with a number of researchers attributing the decline to differences in instructional practices (Eccles, Wigfield, & Schiefele, 1998;Oldfather & McLaughlin, 1993).…”
Section: Self-efficacy and Engagementmentioning
confidence: 99%
“…Teachers must provide ample time for students to think, plan, write, and revise (Oldfather & McLaughlin, 1993). Instruction affords writing in a wide range of alternative genres and topics.…”
Section: Self-expressionmentioning
confidence: 99%